HUBUNGAN MOTIVASI KERJA, PERSEPSI PELUANG PARTISIPASI DAN TINGKAT STRES KERJA PADA KARYAWAN PERGURUAN TINGGI SWASTA - Jembarwati, Otih (PRESTASI, 2013)
This study uses a quantitative method with using regression analysis. Research subject is Semarang University administrative staff with minimum work term for one year, as many 100 administrative staffs. Research hypothesis is the work motivation, and perceptions of participation opportunities affect in the level of stress on employees of the University of Semarang. Regression equation model is obtained as: y = 34,147 + 0,181 x1 â 0,114 x2. From the above results obtained that F calculated = 116,207 with a significance level of p-value = 0,000, so there is a linear relationship, motivations and perceptions of participation opportunities to job stress. As increasing participation opportunities, job stress decreases. While the motivation increases, the job stress is higher. Motivational influence on the level of stress 70,6%, while the determination coefficient describes the participation opportunities and work motivation has contributed 69,9% to the stress levels of employees of private colleges. Empirical average stress level, 71,41 at the interval score of 18 to 90 so that the stress is high. Participation opportunities empirical mean score of 47.17 at intervals score 25 to 125 that are low and work motivation empirical mean at intervals of 64 to 320 is high.Keyword : motivasi kerja, presepsi peluang partisipasi, tingkat stress